From system theory to complexity theory – on the diversity of organization management methods - Zalewska-Turzyńska, Magdalena (Metody i techniki zarządzania. Inspiracje dla teorii i praktyki, 2020)
The management practice is susceptible to fashions due to the desire and need to constantly improve and maintain a competitive advantage. This approach entails a constant desire to innovate, and the theory of complexity has now become one of the newest trends in management that proposes a way to help organizations. Both systems theory and complexity theory were not developed on the basis of management sciences, but are successfully applied in theoretical considerations and in the practice of organization management. This study attempts to justify the thesis that in the area of organizational management methods, the theory of complexity is a consequence of systems theory. The aim of the study is to analyze those management methods (in evolutionary terms) that arose on the basis of systems theory and complexity theory and were and still remain in the arsenal of managers.